Compliance with Lid Hygiene in Patients with Meibomian Gland Dysfunction - Chuckpaiwong V. (2023)
Purpose: To evaluate the level and predictor of compliance with lid hygiene of the patients with meibomian gland dysfunction (MGD) by a specially designed and validated questionnaire. Patients and Methods: A cross-sectional, descriptive study was conducted among patients with symptomatic meibomian gland dysfunction visiting at Ramathibodi Hospital from April 2019 to December 2020. Dry eye symptom, fluorescein tear breakup time (TBUT), ocular surface staining, lid morphology, meibum quality, and meibum expressibility were evaluated. All patients were instructed to perform lid hygiene two times daily. Eight weeks after receiving the instruction, the patients were asked to complete a newly developed seven-item questionnaire to assess compliance. The associated factors limiting treatment adherence were evaluated. Proper statistical analyses were used to determine the relationships between compliance and non-compliance and a group of relevant baseline variables. P < 0.05 was considered to be statistically significant. Results: A total of 77 patients were recruited into the study. Sixty-three patients (81.8%) were female. The mean age was 66.71 ± 8.17 years old (42–87 years). Good compliance with lid hygiene was reported by 42 patients (54.6%). Patient demographic factors or the number of concurrent systemic or ophthalmic drugs were not significantly different between the compliance and non-compliance groups. Some clinical signs, including the higher scores of meibomian gland expressibility and moderate to severe ocular surface staining, were significantly positively associated with lid hygiene compliance (χ2 = 10.13, P = 0.001 and χ2 = 10.48, P = 0.001, respectively). A lack of time was the most notable reason for non-compliance. Conclusion: Approximately half of the patients with symptomatic MGD had good compliance with lid hygiene by the specific questionnaire. Appropriate patient education and optimization methods of lid hygiene may promote patient compliance.